The Employability and Career Development of Finance and Trade College Graduates - Huang, Xiang; Cao, Jiajia; Zhao, Guojing; Long, Zehai; Han, Guanshuang; Cai, Xiaowei (Frontiers in Psychology, 2022)
Employability is a vital aspect for human development in career fields. In order to explore the factors affecting the employability of finance and trade graduates in higher vocational colleges, the researchers focused on human development in educational settings and conducted a quantitative research within 9 higher vocational colleges. The study uses descriptive statistical analysis to demonstrate the sample structure; using t-test, rank sum test and chi-square test to assess the variables. And also adopts exploratory factor analysis to identify the classification of both educational practice and employability. Then, multivariable linear regression model was adopted to examine the relationships between three main factors as well as the employability and career development of finance and trade graduates. The findings imply that finance and trade college graduate soft skills and basic skills have immensely improved by educational practice; graduates with high motivation for learning could enhance their soft skills and more internship or clubs engagement brings stronger professional skills. Based on these results, higher vocational colleges, enterprises, policymakers, teachers and finance and trade graduates will benefit from the findings related to the reform of educational practice for strengthening graduate employability and the human development. The originality of this paper is the conceptual evolution of finance and trade college graduate employability, as well as the empirical analysis on educational practice, student engagement and family background affecting their human development.